Communication, mediatization and virtualization of life: domination and power in illusory freedom - Nogueira, Silas (Revista Extraprensa, 2023)
This article stems from a request for a text produced with content, format and language that could be discussed by undergraduate students and novice researchers. Hence this quick review of communication theories—among some of the best known in the country—aimed at presenting some authors and lines of research to resume critical discussions and contents, as well as to highlight epistemological positions capable of contributing to a critical reading of the complexities of today’s communication and society. Communication, technologies, media, mediatization, (techno)culture and virtualization emerge as concepts (re)appraised and understood as necessary for the continuity of a critical stance.